FLYPAPER EFFECT ON REGIONAL SPENDING IN CENTRAL JAVA PROVINCE - Soeharjoto Soeharjoto; Debbie Aryani Tribudhi; Dini Hariyanti; Rinaldi Rustam; Syofriza Syofyan (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
Implementation of autonomy policies in the reform area aims to accelerate region growth, make Central Java Province continues to optimize their regional spending to increase their development. Purpose of this research is to determine effect of the original local government revenue and general allocation funds to regional spending and flypaper effect existence. Panel data regression and independent sample t test used as a method with 2014-2017 data from 35 districts and cities at Central Java. Result shown that there is positive and significant effect at original local government revenue and general allocation funds to regional spending. However, the construction being carried out still has a flypaper effect